La représentation cinématographique de la peur face à l’étranger - Paola García (Les Cahiers ALHIM)
This article seeks to analyze the way in which the cinema represents the contacts and relationship which are established between foreigners and nationals in the host countries. We will analyze these relations in the movies Un Cuento Chino by Sebastian Borensztein (2011) and The Visitor by Thomas McCarthy (2007), from the notion of symbolic borders developed by Marta Rizo Garcia and Vivian Romeu Aldaya (2006b). We will focus on the communicative interactions that occur between the different actors and especially the process prone to engender the acceptance or rejection of foreigners. We show that these two films which are constructed from the vision of the national, pose the question of the report to « the Other-foreigner » and provoke conflicting emotions between confidence and fear.